Analisis Peran Pendidikan dalam Membentuk Nilai Sosial dan Nilai Budaya Siswa di Sekolah Dasar Kabupaten Ogan Komering Ilir - Windy Anisa Dewi; Fani Rahmasari; Azzahra Nurul Nadilah; Ayu Apriana (Complex : Jurnal Multidisiplin Ilmu Nasional, 2024)
This research aims to describe the role of education in shaping the social and cultural values of students in elementary schools in Ogan Komering Ilir district, Sumatera Selatan. The method used in this research is descriptive qualitative. The data collection techniques used were observation and interviews. The results of this research are the role of education in forming social values and cultural values, teachers' strategies in integrating social values and cultural values in learning, teachers' challenges in forming students' social values and cultural values, as well as examples of social values and cultural values that students must preserve. Education has an important role in forming students' social and cultural values at school. During the learning process, teachers can always remind students of the importance of caring for others so that the goal of maintaining social and cultural values can be realized.